Cavernous Lymphangioma Arising in the Chest Wall 19 Years after Excision of a Cystic Hygroma - Lee, Woo Surng (Korean Society for Thoracic and Cardiovascular Surgery, 2011)
Lymphangioma is a congenital malformation of the lymphatic system and is thought to result from the failure of the lymphatic system to connect with the venous system. Lymphangioma of the chest wall is a very rare disease entity, and only a few cases have ever been documented in the literature. To the best of our knowledge, there have been few cases of recurrent cavernous lymphangioma after surgical excision of a cystic hygroma on the same side of the chest wall. Here, we report a case of a cavernous lymphangioma of the chest wall in a patient who had undergone surgical excision of a cystic hygroma 19 years earlier.